1986
DOI: 10.1007/bf00181230
|View full text |Cite
|
Sign up to set email alerts
|

L-Tryptophan administered to chronic sleep-onset insomniacs: Late-appearing reduction of sleep latency

Abstract: The effects of 3 g L-tryptophan on sleep, performance, arousal threshold, and brain electrical activity during sleep were assessed in 20 male, chronic sleep-onset insomniacs (mean age 20.3 +/- 2.4 years). Following a sleep laboratory screening night, all subjects received placebo for 3 consecutive nights (single-blind), ten subjects received L-tryptophan, and ten received placebo for 6 nights (double-blind). All subjects received placebo on 2 withdrawal nights (single-blind). There was no effect of L-tryptopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In a dose-response study, Hartmann et al (1974) found that 1-15 g of L-Trp decreased sleep latency, but only doses above 5 g increased slow-wave sleep and decreased REM sleep. Other studies have failed to demonstrate modulations to sleep stages (Brown et al, 1979;Spinweber, 1986), which may, in part, be attributed to varying Trp doses. Spinweber (1986) found that 3 g L-Trp did not alter sleep stages or brain electrical activity during sleep in chronic sleep-onset insomniacs.…”
Section: Effect Of Tryptophan Loading On Sleep Parameters In Insomniacsmentioning
confidence: 91%
See 1 more Smart Citation
“…In a dose-response study, Hartmann et al (1974) found that 1-15 g of L-Trp decreased sleep latency, but only doses above 5 g increased slow-wave sleep and decreased REM sleep. Other studies have failed to demonstrate modulations to sleep stages (Brown et al, 1979;Spinweber, 1986), which may, in part, be attributed to varying Trp doses. Spinweber (1986) found that 3 g L-Trp did not alter sleep stages or brain electrical activity during sleep in chronic sleep-onset insomniacs.…”
Section: Effect Of Tryptophan Loading On Sleep Parameters In Insomniacsmentioning
confidence: 91%
“…The bulk of evidence indicates that doses as low as 1 g L-Trp significantly reduce sleep latency and increase subjective ratings of sleepiness in subjects with insomnia (Brown et al, 1979;Hartmann et al, 1974;Hartman and Spinweber, 1979;Kö rner et al, 1986;Spinweber, 1986). Doses below 1 g have shown trends towards decreased sleep latency in mild insomniacs (Hartman and Spinweber, 1979).…”
Section: Effect Of Tryptophan Loading On Sleep Parameters In Insomniacsmentioning
confidence: 95%
“…TRP decreases sleep latency in those with long sleep latencies [10][11][12]. However, TRP is able to give therapeutic improvement in chronic and severe in- Wong/Ong somniacs characterized by both sleep onset and sleep maintenance problems only after several days to weeks of therapy [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In a nighttime study, the sleep-promoting effects of 1-tryptophan 3 g were assessed in a group of chronic, sleep-onset insomniacs (Spinweber, 1986). In this study, 1-tryptophan reduced sleep latency significantly on the fourth through sixth nights of administration.…”
Section: L-tryptophan As a Sleeping Aidmentioning
confidence: 99%